PENINGKATAN KUWALITAS KESEHATAN ANAK DENGAN SKREENING TUMBUH KEMBANG DAN PROMOSI KESEHATAN ( TK AL ISLAMIYAH JOGOROTO JOMBANG) - Ana Farida Ulfa; Kurniawati, Kurniawati; Pujiani, Pujiani; Masruroh, Masruroh; Zuliani, Zuliani; Siti Muniroh; Abdul Ghofar; Zulfikar, Zulfikar; Wim Banu Ukhrowi; Nuroin Farohiyah (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
Children's health is the nation's future asset. The period of child growth has started from the first year of life, especially the period since the fetus is in the womb. Good and sufficient nutrition, good health status, proper parenting, and proper stimulation during this period will help children grow healthy and be able to achieve their optimal abilities. Appropriate stimulation will stimulate the toddler's brain so that the development of movement, speech and language abilities, socialization and independence in toddlers takes place optimally according to the child's age. Structured growth and development screening is an effort to detect early deviations in growth and development in children, so that appropriate treatment can be carried out immediately. Family knowledge, especially mothers in supporting good parenting efforts for children, especially toddlers, greatly supports the success of growth and development in children.Community service activities include; growth and development screening and parenting on growth and development in preschool-aged children. This activity involved 32 children in PAUD and TK Al Islamiyah, and 32 parents (mothers or caregivers) to participate in parenting activities. Growth and development screening uses the KPSP assessment format (Kemenkes RI). Meanwhile, for parenting, the SAP of Health Education and questionnaires were used to assess knowledge before and after receiving parenting. The results of health screening showed that 44% of children had growth and development status in the inappropriate/deviant category, and 34% had poor nutritional status. Mother's knowledge about the growth and development of preschool children increased significantly after getting parenting.Factors causing growth and development status in the inappropriate/deviant category are; nutritional status of children, parental knowledge and lack of parental stimulation of child development tasks. Early detection is expected to be able to become an evaluation so that stimulation of growth and development can be carried out optimally.